Toxicity of three types of arsenolipids: species-specific effects in Caenorhabditis elegans. Issue 5 (31st March 2020) - Bornhorst, Julia; Ebert, Franziska; Meyer, Sören; Ziemann, Vanessa; Xiong, Chan; Guttenberger, Nikolaus; Raab, Andrea; Baesler, Jessica; Aschner, Michael; Feldmann, Jörg; Francesconi, Kevin; Raber, Georg; et al.
Abstract : AsHCs and AsTAG are highly bioavailable to C. elegans., AsHCs are metabolized by C. elegans., AsHCs but not AsTAG and AsFA affect survival and development in C. elegans . Abstract : Although fish and seafood are well known for their nutritional benefits, they contain contaminants that might affect human health. Organic lipid-soluble arsenic species, so called arsenolipids, belong to the emerging contaminants in these food items; their toxicity has yet to be systematically studied. Here, we apply the in vivo model Caenorhabditis elegans to assess the effects of two arsenic-containing hydrocarbons (AsHC), a saturated arsenic-containing fatty acid (AsFA), and an arsenic-containing triacylglyceride (AsTAG) in a whole organism. Although all arsenolipids were highly bioavailable in Caenorhabditis elegans, only the AsHCs were substantially metabolized to thioxylated or shortened metabolic products and induced significant toxicity, affecting both survival and development. Furthermore, the AsHCs were several fold more potent as compared to the toxic reference arsenite. This study clearly indicates the need for a full hazard identification of subclasses of arsenolipids to assess whether they pose a risk to human health.